Lactancia materna y su influencia en el estado Nutricional de lactantes de 0 a 12 meses, controlados en el centro de salud 6 de Octubre del distrito de Belén - Iquitos. Marzo – Agosto 2013 - Terrones Bartra, Jans Paol (2014)
The present study "breastfeeding and its influence on the nutritional status of Infants 0-12 months, controlled in the October 6, Belen - Iquitos District Health Center. March - August 2013 ", descriptive, correlational, quantitative Study with retrospective data collection (expo de facto), whose goal was to Determine the influence of breastfeeding on the nutritional status of infants 0- 12 months, controlled on October 6, the Bethlehem district health center, the Sample was 80 infants and the variables studied were; breastfeeding and Nutritional status. As a result of the socio-demographic characteristics of the mothers of the Infants; He is characterized by having an age 15 to 20 years in 26.25%, but The higher percentage was of 48.75% in the range of ages of 21 to 30 years. The degree of instruction of higher percentage with 70.00% were mothers Who have secondary studies; only the 2.50% do not have any kind of studies.Marital status, with higher percentage are the cohabitants with 50.00%. For Its part the occupation of mothers that prevails with the 81.25% is the Housewife. According to the source the 88.75% comes from the urban area, And the 11.25% of the rural área. The results were that breastfeeding, was obtained that 65 per cent of infants Are fed up to 6 months exclusive breastfeeding. On the other hand, 35% Have preference to breastfeeding more plug-ins. In relation to the variable nutritional status, was obtained as a result 81,25% Of infants with a normal nutritional state, on the other hand, 5.00% is Overweight; 3.75% show obesity and the same percentage 3.75% acute Malnutrition and the 6.25% chronic malnutrition. It is concluded for a security of 95% (α = 0.05) the theoretical value of a Distribution, Chi-square with 4 degrees of freedom is 9.49. As you wish in the Calculation of the χ2 we got a value of 16.6, which exceeds the value for α = 0. 05, the result shows breastfeeding influences the nutritional status. Both Are therefore associated, that leads to the conclusion that if you work one of Them, in this case the lactation, we can improve the nutritional status of Infants treated in the center of health 6 October district of Belen - Iquitos. In The period March - August 2013